STUDY ON SOME PROPERTIES AND MORPHOLOGY OF COMPOSITES BASED ON POLYETHYLENE GRAFTED ACRYLIC ACID/ETHYLENE-VINYL ACETATE COPOLYMER/CALCIUM CARBONATE - Thai Hoang; Do Van Cong (Universitas Gadjah Mada, 2008)
Composites based on polyethylene grafted acrylic acid (PE-g-AAc)/ethylene-co-vinylacetate copolymer (EVA)/calcium carbonate (CaCO3) were prepared by melt mixing. Relative melt viscosity, morphology, mechanical properties and thermostability of the composites were studied. The experimental results show that the presence of (CaCO3) activated by stearic acid (10-20 wt.%) changes lightly stable torque of polymer blend of PE-g-AAc/EVA. Use of modified PE improves compatibility of PE and EVA as well as makes the components disperse into each other better than in blends using unmodified PE. Tensile strength and elongation at break of both polymer blends decrease with presence of CaCO3. However, tensile strength of the composites of PE-g-AAc/EVA/CaCO3 is higher than that of composites of PE/EVA/CaCO3. Beside that, the composites of PE-g-AAc/EVA/CaCO3 have thermostability higher than the composites of PE/EVA/CaCO3.